2012
DOI: 10.1179/1362171812y.0000000041
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on TIG arc welding–brazing of Ti/Al dissimilar alloys with Al based fillers

Abstract: Dissimilar alloys of Ti-6Al-4V and 5A06 Al were butt joined by Al based fillers using a novel TIG welding process, referred to as keyhole arc welding-brazing. The flow behaviour of weld pool was introduced, which was characterised by the formation of a keyhole under the tungsten electrode. It was found that porosity tended to be produced in the middle of the fusion line, while adding elements prevented its formation. At brazing interface, interfacial reaction at root face was enhanced, and a uniform serrated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Subsequently, dissolved Ti atoms react with Al atoms to form TiAl 2 along a liquid/solid interface. The formation of TiAl 3 is suppressed, which would be attributed to fast cooling rate of hybrid welding since the welding speed used in this paper (2.5 m·min −1 ) is even faster than that of the usual single arc and laser welding (<0.3 m·min −1 ) [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, dissolved Ti atoms react with Al atoms to form TiAl 2 along a liquid/solid interface. The formation of TiAl 3 is suppressed, which would be attributed to fast cooling rate of hybrid welding since the welding speed used in this paper (2.5 m·min −1 ) is even faster than that of the usual single arc and laser welding (<0.3 m·min −1 ) [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Titanium is difficult to fusion weld to a nickel base alloy because it forms brittle intermetallic compounds with almost every element contained in such alloys (Ni, Fe, Cr, Mn, and Si). However, the use of buttering (columbium or copper alloy) and better control of welding parameters can improve mechanical properties of the joint (Gorin 1964;Lv et al 2012).…”
Section: Difficulties In Dissimilar Non-ferrous Metal Weldingmentioning
confidence: 99%
“…It was demonstrated that in aluminum-titanium dissimilar weld, porosity tended to be produced in the fusion line. It happens that gases in the seam are hard to escape and concentrated in the middle of fusion line during the solidification process [21]. In Figure 6, some gas trapping occurred on both sides of the intermetallic layer but not in the intermetallic layer.…”
Section: Metallurgical Characterization Of Weldmentioning
confidence: 99%